(untitled) (The Pakistan Development Review, 1992)
This paper examines the subordination of women by men among the populations of the Northern Areas of Pakistan. The examination is undertaken with reference to the Chalt-Chaprote community in the Nagar Valley, where fieldwork was conducted in 1989-90. Hence, we: (a) Analyse the manner in which the subordination of women is manifested, and reinforced during different socioeconomic activities; and (b) Determine the effects, or lack of effect, on the status and role of women, of changing conditions (as a consequence of increased incorporation of the region in which the community is located, within the political economy).